Correlation between transverse and sagittal dimensions in early stage: a retrospective study between patients treated with clear aligners and untreated patients - Simonetta Meuli; Davide Gentile; Daniele Garcovich; Luca Giuliante; Edoardo Staderini; Massimo Cordaro (BMC Oral Health)
Abstract Background The interceptive treatment of Class II malocclusion using clear aligners is still debatable. This retrospective study analyzes the short-term occlusal and cephalometric effects in 40 growing patients with Class II malocclusion. Methods The sample was divided into 2 groups: Following the dentoalveolar expansion protocol, the first group was treated with clear aligners (GI). The second group was untreated (GN). Dental arches were scanned before and 1 year after the therapy. Similarly, linear measurements on digital casts and cephalometric ones on lateral X-rays were compared. Maxillary (Lmax), mandibular intermolar length (Lmand), and posterior transverse intermolar discrepancy (DIT) were evaluated. The distance between the mesiobuccal cusp of the upper first molar and the buccal groove of the first lower molar was considered at both sides (Cdx and Csx). The statistical descriptive analysis of T0 and T1 values was performed using a paired t-test, setting a p value < 0.05. Results A greater improvement in molar and skeletal Class II parameters in the GI group compared to the GN group was detected. Specifically, in GI, Lmax improved by 3.3 mm, Lmand by 1.1 mm, and DIT improved from − 2.1 mm to 0.1 mm, while Cdx and Csx decreased by 1.28 mm and 1.13 mm, respectively. In contrast, the GN group showed smaller improvements, with Lmax increasing by 1 mm, Lmand by 0.8 mm, DIT improving from − 2 mm to -1.8 mm, and both Cdx and Csx exhibiting slight increases of 0.04 mm and 0.09 mm, respectively. No statistically significant differences were observed regarding divergence or the correlation between skeletal and dental measurements. Conclusions Dentoalveolar expansion using Invisalign First appears effective and predictable with better outcomes than the control group. An improvement of skeletal Class II is detected in the treated group with dental improvements on maxillary arch.